Technical and physical demands of small vs. large sided games in relation to playing position in elite soccer - Dellal, A.; Owen, A.; Wong, D. P.; Krustrup, P.; van Exsel, M.; Mallo, J. (Human Movement Science, 2012)
The aim of this investigation was to compare the effects of common rule changes on technical and physical demands for elite soccer players in five playing positions during various 4-min small-sided games (SSGs) in comparison to 11-a-side matches. Forty international players classified into five positional roles participated in the study (25.3 ± 2.4 years, 182.4 ± 2.3 cm, 77.3 ± 4.1 kg; M ± SD). Players completed three different conditioned small-sided 4 vs. 4 games (1 ball touch = 1T, 2 ball touches = 2T and Free Play = FP) as well as two friendly matches. Heart rate (HR), blood lactate ([La]), ratings of perceived exertion (RPE) as well as physical and technical performance were analyzed. Compared to match-play, total distance covered per minute of play, high-intensity running activities (sprinting and high-intensity runs), total numbers of duels and lost ball possessions were significantly greater within SSGs for all playing positions (p < .05). In contrast, [La], percentage of successful passes and number of ball possessions were lower (p < .05) within SSGs, particularly with 1T and 2T rules, in comparison with match-play. HR was higher in SSGs compared to match-play for all playing positions, and RPE values were lower (p < .05) during the FP SSG for defensive midfielders, wide midfielders and forwards. In conclusion, this study revealed that 4 vs. 4 SSGs played with 1 or 2 ball touches increased the high-intensity running and the difficulty to perform technical actions, being more specific to match demands. Subsequently, it is of importance for coaches to understand the different physiological demands imposed upon players by varying the rules of SSGs and to understand the differences between positional roles.